“FROM ZERO to BISA” PEMBERDAYAAN IBU-IBU RUMAH TANGGA: TRANSFORMASI TALAS GANDOANG MENJADI SUMBER PENGHASILAN BARU DI GANG DESA, CILEUNGSI, KABUPATEN BOGOR - Selfiana, Selfiana; Listiorini, Dewi; Herryani, Herra; Safrani, Audy Lea; Anggi Haryadi; Rizki, Encik Daffa; Sukandriyo, Mayudi (Jurnal Abdi Insani, 2025)
Gang Desa (formerly Gang Coklat) is a settlement in Limus Nunggal Village, Cileungsi, near the elite area of Kota Wisata Cibubur. Behind the splendor of Kota Wisata, the residents of Gang Desa live on low incomes. The lack of knowledge and skills in processing food based on local agricultural products for their children's snacks, makes them in an urgent situation to be able to acquire economically valuable skills that can be managed together. This PKM aims to empower housewives to process healthy and ready-to-eat foods from taro gandoang and turn them into culinary businesses to earn additional income. The activity was carried out from May to September 2025, attended by 20 fostered partners divided into two Joint Business Groups. The methods applied were socialization, namely education about healthy and nutritious food; training included practical processing of ingredients, marketing theory: branding, logos, product names and packaging; digital marketing technique theory: practical culinary content creation, and theory of calculating the cost of goods sold. After several training sessions and repetitions of processing basic taro ingredients into delicious and economically valuable foods, partners appeared to be skilled at practicing the recipes taught. Furthermore, they understand the importance of branding, logos, product naming, and food packaging techniques, as well as calculating Cost of Goods Sold and creating culinary containers. However, due to limited mobile phone availability, not all partners are proficient in culinary content creation. This program has successfully motivated partners to create culinary businesses using taro gandoang as a base ingredient, with support from implementing partners. Keywords: taro gandoang, digital marketing, Cost of Goods Sold.